Pyridoxine-dependent early onset seizures associated with rare gene mutations: a case series - Ali Hyder Nazeer; Durray Shahwar Abid Khan; Prem Chand (Journal of the Pakistan Medical Association, 2025)
Pyridoxine dependent epilepsy (PDE) is a rare autosomal recessive disorder. Several genes involved in Pyridoxine (B6) metabolism have been implicated in the pathogenesis of PDE, two such genes are Aldehyde Dehydrogenase 7 Family Member A1 (ALDH7A1) and Pyridox(am)ine 5’-phosphate oxidase (PNPO). To add to the limited data on PDE, three cases of Vitamin B6 dependent neonatal epilepsy caused by pathogenic variation in the ALDH7A1 and PNPO genes are reported. PDE is a rare, but potentially debilitating, cause of neonatal-onset epilepsy. Keeping in view the variable presentations of this condition, patients with a clinical picture suggestive of PDE must be carefully evaluated and treatment initiated as early as possible to achieve the best outcomes. Keywords: Pyridoxine, Epilepsy, ALDH7A1 and PNPO.